Method for producing sheet metal component from flat steel product provided with corrosion-protective coating

By adopting four continuous furnace zone annealing and Al-based corrosion protection coating methods in the manufacturing process of flat steel products, the resistance welding and paint adhesion of flat steel products are optimized, and the welding of plate members in the prior art is solved. and adhesion issues have achieved better coating performance and component quality.

CN119242903APending Publication Date: 2025-01-03THYSSENKRUPP STEEL EUROPE AG PATENTE PATENT DEPARTMENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411254539.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-06-03
Filing Date
2020-05-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art is difficult to meet the high requirements for flat steel product sheet members in terms of resistance welding and organic layer adhesion, especially for paint adhesion, and cannot effectively control the surface properties and composition of the corrosion protection coating.

Method used

By using four continuous furnace zone annealing and Al-based corrosion protection coating methods when manufacturing flat steel products, the annealing atmosphere and temperature are controlled to form a pure iron surface and the introduction of alkaline earth metal or transition metal into the coating, optimized The structure and conductivity of the iron-aluminum layer reduces pores in the coating and improves the uniformity and adhesion of the coating.

Benefits of technology

The optimization of resistance welding performance of sheet members and the improvement of organic coating adhesion is achieved, which significantly reduces the number of holes in the coating, improves the welding performance and paint adhesion of the components, and meets the demand for high adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242903A_ABST
    Figure CN119242903A_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing a sheet metal component, wherein a) a flat steel product made of steel is provided; b) annealing the flat steel product in a continuous furnace with four areas A, B, C and D; c) applying a corrosion protective coating to the flat steel product; optionally d) flattening the rolled flat steel product; e) dividing the slab from the flat steel product; f) heating the flat steel product for a holding duration to > Ac3 temperature of the steel of the flat steel product and < 1000 DEG C; g) thermoforming the flat steel product into a sheet component; h) cooling at least one section of the component at a cooling rate sufficient to produce a quenched structure. The invention also provides a component, wherein an optimized adhesion of the corrosion protection coating on the steel substrate is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for producing a sheet metal component from a flat steel product, which has a corrosion protection coating. Background Art

[0002] In this case, a “flat steel product” is understood to be a rolled product whose length and width are each significantly greater than its thickness, including in particular steel strips and steel sheets.

[0003] In this text, the statements about the contents of alloying components are always given in % by weight, unless expressly stated otherwise.

[0004] Instead, the proportions of specific components in the atmosphere, in particular in the annealing atmosphere, are given in % by volume unless otherwise stated.

[0005] A method of the type described at the outset is known from EP 2 993 248 A1. A flat steel product is used as the starting product for this method, the steel substrate of which consists of a so-called "MnB steel". Such steels are standardized in EN 10083-3 and have good hardenability. Here, they allow reliable process control during hot pressing, by which process control it is possible to achieve in an economical manner that martensitic hardening is also caused in the tool during hot deformation without additional cooling. A typical example of such a steel is the steel known under the name 22MnB5, which is listed in Steel Key (Stahlschlüssel) 2004 under material number 1.5528. Typically, the fully killed 22MnB5 steel available on the market contains, in addition to iron and unavoidable impurities (in wt. %), 0.10-0.250% C, 1.0-1.4% Mn, 0.35-0.4% Si, up to 0.03% P, up to 0.01% S, up to 0.040% Al, up to 0.15% Ti, up to 0.1%

[0006] Nb and a total of up to 0.5% Cr+Mo, and up to 0.005% B. In order to protect the flat steel products made of such steel from corrosive attack and at the same time minimize the risk of hydrogen absorption during the heating required for hot forming, the flat steel products according to the known method are provided with an Al-based corrosion protection coating, which contains at least one alkaline earth metal or transition metal in an effective content of 0.005-0.7% by weight as an additional alloying component. In addition, a Si content of 3-15% by weight and a Fe content of up to 5% by weight may also be present in the coating. Here, as at least one alkaline earth metal or transition metal of the protective coating, Mg in a content of 0.1-0.5% by weight is preferably used, wherein calcium, strontium, sodium or barium may also be considered as an alternative or in addition. The aluminum-based protective coating can be applied to the steel substrate by melt-dip coating (also called "hot-dip aluminum" in industry terminology) or by a gas deposition method, such as the known PVD method (physical vapor deposition) or CVD method (chemical vapor deposition).

[0007] The special requirements for the manner and method of applying the corrosion protection coating to the steel substrate consisting of MnB steel are not mentioned in the above-mentioned prior art. Here, when the slab coated in the above-mentioned method is heated to a temperature of 900° C. in a standard atmosphere for a period of 360-800 seconds, the presence of alkaline earth metals or transition metals in the coating can minimize the absorption of hydrogen in the steel substrate and thus minimize the risk of so-called "hydrogen embrittlement".

[0008] However, in practical use, components formed from flat steel products produced by the above-described method, although successful, i.e. with optimized strength, have been found not to always meet the increasingly stringent requirements placed on these sheet metal components with regard to their behavior in resistance welding and their adhesion to organic layers (e.g. paint or the like).

[0009] DE 10 2017 210 201 A1 likewise relates to a method for producing an Al-based steel component provided with a metallic coating for protection against corrosion. For this purpose, a flat steel product is provided which consists, in wt. %, of 0.15 to 0.50% C, 0.50 to 3.0% Mn, 0.10 to 0.50% Si, 0.01 to 1.00% Cr, up to 0.20% Ti, up to 0.10% Al, up to 0.10% P, up to 0.1% Nb, up to 0.01% N, up to 0.05% S and up to 0.1% B, the remainder being Fe and unavoidable impurities, and is coated with an Al coating which consists, in wt. %, of 3 to 15% Si, 1 to 3.5% Fe, up to 0.5% alkali metals and / or alkaline earth metals, the remainder being Al and unavoidable impurities. The provided sheet is annealed in a furnace at a certain temperature and for a certain duration, which are related to each other by parameters calculated according to complex formulas. Here, depending on the furnace residence time and the temperature, a so-called interdiffusion zone should be formed at the transition between the substrate and the coating, in which no martensitic structure appears during press quenching, and which does not belong to the Al coating. This interdiffusion zone extends from the middle of the flat steel product from a thickness (from which martensite is no longer present in the component) to a thickness from which the Al coating has an iron content of ≤85% by weight and an Al content of ≥10% by weight. In this prior art, there is no indication of how the interdiffusion zone can be specifically constructed, or guidance on how the occurrence and composition of the interdiffusion zone can be controlled in a targeted manner with respect to the specific surface properties of the coating. On the contrary, in this document, it is important to consider the improvement of the deformation behavior of the Al coating, in particular the achievable bending angle. Summary of the invention

[0010] Against this background, the object of the present invention is to provide a method for forming a sheet metal component from a flat steel product of the type mentioned above, which sheet metal component meets the very high demands on its weldability and has optimal conditions for coating with an organic coating, in particular for painting.

[0011] To achieve this object, the present invention proposes that, when manufacturing a sheet metal component, at least the method steps specified in claim 1 are performed.

[0012] It goes without saying that when implementing the method according to the invention, a person skilled in the art not only carries out the method steps mentioned in the claims and explained here, but also, if necessary for this, all other steps and operations which are usually carried out in the actual implementation of such methods in the prior art.

[0013] Advantageous embodiments of the invention are specified in the dependent claims and are explained in more detail below as a general inventive concept.

[0014] Therefore, in the method according to the invention for producing a sheet metal component from a flat steel product provided with a corrosion protection coating, at least the following working steps are performed:

[0015] a) providing a flat steel product, the flat steel product being produced from a steel comprising, in wt. %, 0.05-0.5% C, 0.5-3% Mn, 0.06-1.7% Si, up to 0.06% P, up to 0.01%

[0016] S, up to 1.0% Al, up to 0.15% Ti, up to 0.6% Nb, up to 0.01% B, up to 1.0% Cr, up to 1.0% Mo, up to 1.0% Cr and Mo in total, up to 0.2%

[0017] Ca, up to 0.1% V and the balance iron and unavoidable impurities;

[0018] b) annealing the flat steel product in a continuous furnace having four zones A, B, C and D, through which the flat steel product passes continuously and in which the flat steel product has a dew point temperature TP A TP B TP C TP D The annealing temperature is GT A GT B GT C GT D Annealing, the annealing atmosphere consists of 0.1-15 volume % hydrogen and the balance nitrogen and technically unavoidable impurities, satisfying the following conditions:

[0019]

[0020]

[0021] c) applying a corrosion protection coating to the flat steel product obtained in working step b), wherein the corrosion protection coating consists, in wt. %, of up to 15% Si, up to 5% Fe, in total 0.1-5% of at least one alkaline earth metal or transition metal and the remainder Al;

[0022] d) Optionally: temper rolling of the flat steel product provided with a corrosion protection coating;

[0023] e) optionally: dividing slabs from the flat steel product;

[0024] f) heating the flat steel product or slab to a hot forming temperature which is above the Ac3 temperature of the steel of the flat steel product and does not exceed 1000° C. for a holding time which is sufficient to introduce a thermal energy Js of more than 100 000 kJs and not more than 800 000 kJs into the flat steel product or slab;

[0025] g) hot forming a flat steel product heated to a hot forming temperature or a slab heated to a hot forming temperature into a plate component;

[0026] h) cooling at least a section of the component at a cooling rate sufficient to produce a quenched structure in the section of the sheet material component.

[0027] The invention is based on the recognition that the behavior of sheet metal components provided with a corrosion protection coating based on aluminum (“Al-based”) during resistance welding and the adhesion of organic coatings, in particular paints, on these sheet metal components do not depend solely on the composition of the boundary layer between the corrosion protection coating and the ambient atmosphere, but that in particular parameters such as the roughness and conductivity of the entire coating also play a decisive role. The prerequisite for an optimally homogeneous corrosion protection coating to be present in the component processed in accordance with the invention is achieved by annealing (working step b)) before applying the corrosion protection coating (working step c)).

[0028] Therefore, the components produced according to the invention typically have a corrosion protection coating that consists of a plurality of layers of different compositions. By controlling the dew point temperature and the annealing temperature during annealing in a continuous annealing furnace according to the invention for the preparation of the subsequent application of the corrosion protection coating, a significant reduction in the pores contained in the coating is achieved.

[0029] The annealing parameters selected according to the invention in the annealing prior to coating (step b)) achieve that pure iron ("Fe") is present on at least 70% of the surface of the completely annealed flat steel product. This results in a good connection to the subsequently applied Al-based coating, wherein an iron-aluminum layer ("Fe-Al layer") is formed at the transition from the steel substrate to the corrosion protection coating. On the other hand, this results in a sufficient and uniform distribution of the iron in the layer, thereby improving the conductivity of the layer and, as a result, optimizing the behavior of the resistance welding.

[0030] If the flat steel product provided in step b) is already a blank suitable for forming into a component, step e) can be omitted. If, on the other hand, the flat steel product provided is a steel strip or a larger steel sheet, it is cut into slabs of suitable size in step e).

[0031] The flat steel product annealed and coated in the manner according to the invention (working step b), c)) or the sheet cut therefrom (working step e)) is heated to a hot forming temperature (step f)) for hot forming (step g)). In this case, the iron already present in the uniform boundary layer of the corrosion protection coating can diffuse evenly into the coating without causing noticeable defects. At the same time, the alkaline earth metal or transition metal provided in the corrosion protection coating according to the invention diffuses to the surface due to its oxygen affinity and forms an oxide layer there. In this case, the iron atoms can exchange positions with alkaline earth metal atoms or transition metal atoms in a ratio of 1:1 due to their comparable atomic size and thus be introduced into the metal lattice, so that the diffusion of the alkaline earth metal or transition metal can also lead to the occurrence of a negligible number of defects. Due to the reduction of defects achieved according to the invention, these defects in the corrosion protection coating of the component according to the invention also do not agglomerate into pores, so that the component according to the invention is characterized by a significantly reduced number of pores compared to conventionally produced components, for example, components produced according to the template of EP 2 086 755 B1.

[0032] The effect of the inventive use occurs particularly reliably when the alkaline earth metal or transition metal additionally present is magnesium (“Mg”), i.e. when Mg is present in the content provided according to the invention in the corrosion protection coating applied according to the invention of the processed flat steel product according to the invention, either alone or in combination with further elements belonging to the group of alkaline earth metals or transition metals.

[0033] The method according to the invention is suitable for producing components from flat steel products having a wide range of thicknesses. Thus, flat steel products having a thickness of 0.6-7 mm can be processed using the method according to the invention.

[0034] The production of the flat steel product provided in working step a) can be carried out in any manner known from the prior art. The method according to the invention is particularly suitable for processing flat steel products with a thickness of 0.8-4 mm, in particular 0.8-3 mm. Thicker flat steel products with a thickness of more than 3 mm are typically processed in the hot-rolled state, while thinner sheets are typically provided in the cold-rolled state.

[0035] For the method according to the invention, in working step a), flat steel products can also be provided, which have different thicknesses due to flexible or partial rolling in length and / or width. It is also possible for the method according to the invention to be produced in working step a) from different sheet metal blanks welded together or from flat steel products of the same composition welded together and from steel strips, and together form a flat steel product to be processed for the process according to the invention.

[0036] The corresponding flat steel product provided according to the invention consists of steel having a typical composition of MnB steel, which typically has a yield strength of 250-580 MPa and a tensile strength of 400-720 MPa in the delivery state.

[0037] Therefore, according to the invention, a flat steel product is provided which consists of:

[0038] - 0.05-0.5 wt. % carbon ("C"), wherein the C content is preferably 0.07-0.4 wt. %,

[0039] - 0.5-3 wt. % manganese ("Mn"), wherein the Mn content is preferably 0.8-2.5 wt. %, in particular 1.0-2.0 wt. %,

[0040] 0.06-1.7 wt. % silicon ("Si"), wherein the Si content is preferably 0.06-1.1 wt. %, in particular 0.06-0.9 wt. %,

[0041] - up to 0.06% phosphorus ("P"), wherein the P content is up to 0.03% by weight

[0042] - up to 0.01 wt. % sulfur ("S"),

[0043] - up to 1.0 wt. % aluminum ("Al"), wherein the Al content is preferably at most 0.5 wt. %, in particular at most 0.1 wt. %,

[0044] - up to 0.15 wt. % titanium ("Ti"),

[0045] - up to 0.6 wt. % niobium ("Nb"), wherein the Nb content is preferably up to 0.1 wt. %,

[0046] - up to 0.01 wt. % boron ("B"), wherein the B content is preferably up to 0.005 wt. %,

[0047] - up to 1.0 wt. % chromium ("Cr"), wherein the Cr content is preferably up to 0.5 wt. %, in particular up to 0.2 wt. %,

[0048] - up to 1.0 wt. % molybdenum ("Mo"), wherein the Mo content is preferably up to 0.5 wt. %, in particular up to 0.2 wt. %,

[0049] - Wherein for the Cr content %Cr and Mo content %Mo it is applicable

[0050] %Cr+%Mo≤1wt%,

[0051] - optionally, up to 0.2 wt. %, in particular up to 0.1 wt. % calcium ("Ca"),

[0052] - optionally, up to 0.1 wt. % vanadium ("Va"),

[0053] and the remainder of iron and inevitable impurities.

[0054] Of particular interest for practice, due to their property characteristics, in particular their potential for developing high strength in the final hot-formed and cooled components, are flat steel products composed in a manner known per se: 0.07-0.4 wt. % C, 1.0-2 wt. % Mn, 0.06-0.4 wt. % Si, up to 0.03 wt. % P, up to 0.01 wt. % S, up to 0.1 wt. % Al, up to 0.15 wt. % Ti, up to 0.6 wt. % Nb, up to 0.005 wt. % B, up to 0.5 wt. % Cr, up to 0.5 wt. % Mo, the sum of the contents of Cr and Mo being a maximum of 0.5 wt. %, the remainder being iron and unavoidable impurities.

[0055] This includes steels already in series use which consist of 0.07-0.4 wt. % C, 1.0-1.5 wt. % Mn, 0.3-0.4 wt. % Si, up to 0.03 wt. % P, up to 0.01 wt. % S, up to 0.05 wt. % Al, up to 0.15 wt. % Ti, up to 0.6 wt. % Nb, up to 0.005 wt. % B, up to 0.5 wt. % Cr, up to 0.5 wt. % Mo, the sum of the Cr and Mo contents being a maximum of 0.5 wt. %, the remainder being iron and unavoidable impurities. Steels of this composition achieve a tensile strength of up to 2000 MPa after hot forming and cooling.

[0056] As already mentioned, by annealing (working step b)) carried out in four uninterrupted successive stages A, B, C, D, a surface which is as completely occupied as possible (i.e. at least 70%, in particular at least 80% or at least 90%) by pure Fe is produced on the correspondingly processed flat steel product. For this purpose, specially defined dew point temperatures and annealing temperatures are respectively set in the zones AD of the continuous annealing furnace according to the invention for annealing.

[0057] The annealing in the regions AD in working step b) is carried out in each case in an annealing atmosphere containing 0.1 to 15% by volume of hydrogen, the remainder correspondingly consisting of nitrogen and unavoidable impurities, wherein the sum of the impurities is typically not more than 5% by volume, in particular not more than 4% by volume or preferably not more than 3% by volume.

[0058] All references to the annealing temperature GT below and in the claims A GTB GT C and GT D The statements made are based on the average furnace temperature during the strip passage.

[0059] At the surface of the flat steel product provided according to the invention before entering zone A of the continuous furnace operated according to the invention, various oxidation products are present, which have a negative effect on the quality of the coating and in particular on the formation of pores in the coating. The continuous annealing according to the invention converts these oxides so that, in a technical sense, only iron is present at the surface of the flat steel product after the annealing.

[0060] By setting the dew point temperature TP in zone A of the continuous furnace A Set the annealing temperature to -10°C to -25°C and GT A The annealing temperature GT is set at 800-950°C to cover the oxides present on the flat steel product with iron oxide. In order to achieve this in a particularly targeted manner, in zone A of the continuous furnace, the annealing temperature GT A Can be 810-940℃ and dew point temperature TP A It can be -15 to -25°C.

[0061] In regions B and C, the iron oxide is reduced, so that after region C, iron is present at the surface. For this purpose, in region B, the dew point temperature TP of the annealing atmosphere present there is set to B Lower the annealing temperature to -27°C to -41°C and set the annealing temperature to GT B 800-930° C., wherein in view of the desired effect, it has proven particularly reliable to anneal in zone B of the continuous furnace during the annealing performed in step b) at a temperature of GT B It is 800-900℃.

[0062] In region C, the dew point temperature TP of the annealing atmosphere there is controlled C The annealing temperature is further reduced to -30°C to -80°C, and the annealing temperature GT C Maintain at 800-950°C to complete the reduction of iron oxide to iron. When the annealing is completed in step b) at the annealing temperature GT in zone C of the continuous furnace C is 800-920℃, and the dew point temperature TP C This effect can be achieved particularly reliably at a temperature of -30°C to -50°C.

[0063] In region D, the dew point temperature TP of the annealing atmosphere there is controlled D Increase the annealing temperature to -30°C to -20°C and GT DThe temperature is kept at 750-950° C. in order to temper the flat steel product in such a way that, on the one hand, its recrystallization can take place and, on the other hand, the previously obtained pure iron surface is retained. When the annealing is completed in step b) at the annealing temperature GT in zone D of the continuous furnace D This effect can be achieved particularly reliably at a temperature of 780-930°C.

[0064] The lambda value λ describes the mass ratio of air to fuel introduced into the continuous furnace and is typically between 0.95 and 1.1 in the annealing atmosphere maintained in the zone AD of the continuous furnace used according to the invention in the annealing carried out in working step b) of the method according to the invention.

[0065] The effect achieved according to the invention is premised on the presence of at least one alkaline earth metal or transition metal in the corrosion protection coating based on aluminum ("Al") applied after the annealing according to the invention (working step b). Thus, at least 0.1-5% by weight of at least one alkaline earth metal or transition metal and the remainder of Al and unavoidable impurities are present in the coating of the flat steel product treated according to the invention after the application of the corrosion protection coating (working step c) and before the heating for hot forming (working step f)). Here, an alkaline earth metal or transition metal content of at least 0.11% by weight has proven to be particularly advantageous in terms of reliability, so that the positive effect of the presence of at least one alkaline earth metal or transition metal can be used in the coating applied according to the invention. In the case of an alkaline earth metal or transition metal content of more than 5% by weight, increased oxide formation occurs in the melting crucible, which reduces the surface quality. Excessive oxide formation also occurs during hot forming, which, on the one hand, promotes the decomposition of water into hydrogen and oxygen and, as a result, is accompanied by an increased risk of hydrogen entering the steel. On the other hand, thicker oxide layers can lead to high contamination in the forming tool. In order to reliably avoid this effect, the content of alkaline earth metals or transition metals in the corrosion protection coating applied in working step c) can be limited to a total of maximum 1.5% by weight, in particular to a maximum of 0.6% by weight. The alkaline earth metal or transition metal content of the corrosion protection coating applied in working step c) is therefore in particular 0.11-1.5% by weight or in particular 0.11-0.6% by weight.

[0066] As already mentioned, Mg from the group of alkaline earth metals or transition metals has proven to be particularly suitable for the purposes of the invention, which may be present in the coating applied according to the invention alone or in combination with other alkaline earth metals or transition metals such as beryllium, calcium, strontium and barium in order to be able to utilize the effects sought according to the invention.

[0067] Optionally, the coating applied in working step c) may contain a silicon ("Si") content of up to 15% by weight, in particular up to 11% by weight, in order to facilitate the formation of an iron-aluminum layer which adheres well to the iron surface provided in working step b) and which hereby accounts for up to one third of the total layer thickness of the coating. In the case of too high a Si content, an excessively large alloy layer thickness would result, which in turn could lead to a loss of adhesion. In this respect, a Si content of at least 3% by weight, in particular at least 8.5% by weight, has proven to be particularly advantageous, so that in the case of a Si content of 3-15% by weight, in particular 3-11% by weight, in particular 8.5-11% by weight, the positive influence of Si can be utilized particularly reliably in practice.

[0068] Likewise optionally additionally, Fe may be present in the coating applied in working step c) in a content of up to 5% by weight, in particular up to 4% by weight, in particular up to 3.5% by weight. The iron is provided in such an amount in the coating because this is the saturation value for aluminum melts in the temperature range of 650-720° C. By the targeted addition of iron to the melt, the risk of dissolution of iron-containing parts of the melting crucible that are in contact with the melt can be reduced. An Fe content of at least 1% by weight has proven to be particularly advantageous in this respect, so that at an Fe content of 1-5% by weight, in particular 1-4% by weight, in particular 1-3.5% by weight, the positive influence of Fe can be utilized particularly reliably in practice.

[0069] The corrosion protection coating can be applied in any known manner in working step c) of the method according to the invention. In particular, so-called "hot-dip aluminizing" is suitable, in which the individual flat steel products are passed through a suitably heated molten bath composed in accordance with the conditions of the invention. This hot-dip coating is particularly suitable for strip-shaped flat steel products with a thickness of up to 3 mm. In the case of greater thicknesses, one of the vapor deposition methods (PVD, CVD) already mentioned at the outset can also be used to apply the corrosion protection coating.

[0070] The coverage weight of the corrosion protection coating applied according to the invention in working step c) is typically 30-100 g / m per side. 2 , especially 40-80g / m 2 The coverage weight thus present when coating on both sides is 60-200 g / m 2 .

[0071] After the application of the corrosion protection coating (working step c)), the correspondingly coated flat steel product can optionally be subjected to temper rolling (working step d)) in order to set the mechanical property values ​​of the flat steel product, set its surface roughness or homogenize it. The degree of forming set for this purpose (forming degree=(thickness before temper rolling-thickness after temper rolling) / (thickness before temper rolling)) is typically 0.1%-5%.

[0072] After application of the corrosion protection coating (working step c)) or optionally temper rolling (working step d)), the flat steel product is cut, if necessary, in a manner known per se into slabs whose dimensions are matched in a known manner to the dimensions of the sheet metal components to be hot-formed therefrom (working step e)).

[0073] The flat steel product itself or the slab is then heated in working step f) to a hot forming temperature which is higher than the Ac3 temperature of the steel of the flat steel product and does not exceed 1000° C., in particular at least equal to the Ac3 temperature + 50° C. and up to 980° C., wherein a hot forming temperature of 820-950° C. has proven to be particularly advantageous. The flat steel product is kept at this temperature until sufficient heat is introduced into the flat steel product or the slab cut therefrom. The holding time and annealing temperature specifically required in each case can be estimated by means of the following condition, that the thermal energy Js introduced into the flat steel product or the slab in working step f) should be greater than 100 000 kJs and up to 800 000 kJs, wherein Js can be calculated according to the following known formula:

[0074] Js[kJs]=[(T2-T1)xcxtxm] / 1000;

[0075] in,

[0076] T2: The final temperature of the component at the end of heating in K

[0077] T1: Starting temperature of the component in K at the beginning of heating

[0078] c: heat capacity of steel (typically 460 J / kgK)

[0079] t: holding time in seconds of the flat steel product or slab at the final temperature

[0080] m: mass of the flat steel product or slab in kg

[0081] The heating can be carried out in any suitable manner. When using a conventional continuous furnace for this purpose, in which the flat steel product or slab is heated by radiant heat, a suitable holding period is typically 100-900 s, preferably 180-720 s, in particular 240-600 s. When a hot forming temperature of 850-930° C. is selected, a holding period of 180-600 s, in particular 240-600 s, has generally been found to be sufficient in practice. As an alternative to using a continuous furnace, the heating can also be carried out in a conventional chamber furnace, for example.

[0082] The heating of the flat steel product or the slab can also be carried out in a known manner in two steps, firstly to obtain a pre-alloying of the corrosion protection coating and then to bring the flat steel product or the slab to the corresponding hot forming temperature.

[0083] The plate blank or the flat steel product heated to the hot forming temperature is introduced into a hot forming tool within a transfer time of typically less than 15 seconds, in particular less than 10 seconds, and hot formed there into a component (step g)).

[0084] Subsequently or simultaneously, at least one section of the obtained component is cooled in a controlled manner known per se, in order to produce the desired structure in the relevant section of the component. The cooling rate required for this is typically 20-500 K / s, wherein cooling rates of more than 30 K / s, in particular more than 50 K / s, are particularly practical. Here, cooling by "at least one section" naturally also includes the possibility that the component as a whole is cooled in the manner described, in order to produce a quenched structure in the entire component.

[0085] The method according to the invention enables the production of sheet metal components made of flat steel products, the steel substrate of which consists of steel which, in wt. %, consists of: 0.05-0.5% C, 0.5-3% Mn, 0.06-1.7% Si, up to 0.06% P, up to 0.01% S, up to 1.0%

[0086] Al, up to 0.15% Ti, up to 0.6% Nb, up to 0.01% B, up to 1.0% Cr, up to 1.0% Mo, wherein the sum of the contents of Cr and Mo is up to 1.0%, up to 0.2% Ca, in particular up to 0.1% Ca, up to 0.1% V and the remainder of iron and unavoidable impurities, and the steel substrate is coated with a corrosion protection coating, which is composed, in weight %, of up to 15% Si, up to 5% Fe, at least one alkaline earth metal or transition metal in a total amount of 0.1-5 wt. % and the remainder Al and unavoidable impurities, wherein the layer of the corrosion protection coating adjacent to the steel substrate is a boundary diffusion layer consisting of ferrite with an Al content of up to 50 wt. %, in particular at least 1 wt. % Al, wherein in the cross section of the boundary diffusion layer, the proportion of the area occupied by pores with a diameter of ≥ 0.1 μm is less than 10%, in particular less than 5%, preferably less than 3%, and wherein over a measuring length of 500 μm, the area occupied by the pores in the boundary diffusion layer is <300 μm 2 , especially less than 200μm 2 , particularly preferably less than 100 μm 2 The thickness of the alloy layer is 1-30 μm, preferably 2-20 μm, in particular 4-16 μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0087] The invention is explained below with the aid of examples.

[0088] Figure 1 A cross-sectional view of a steel sheet of a sheet metal component produced according to the invention by hot forming is shown at a magnification of 500. The cross-sectional view has been etched in a conventional manner with 3% nitric acid in order to clarify the layer structure present on the steel sheet.

[0089] Figure 2 Shown in accordance with Figure 1 Schematic diagram of the cross section. DETAILED DESCRIPTION

[0090] Therefore, the corrosion protection coating K formed on the steel substrate S includes a boundary diffusion layer D directly adjacent to the steel substrate S, which is essentially composed of α mixed crystals (i.e. ferrite) with an increased Al content. Here, Fe2Al5 is still present in stages. The boundary diffusion layer D is characterized in that it is uniformly and evenly structured and exists almost without pores.

[0091] A first Si-rich layer S1 is formed on the diffusion layer D in the direction toward the free surface O of the corrosion protection coating K. At the boundary between the diffusion layer D and the Si-rich layer S1, pores P1 exist in the diffusion layer D in a small number and at a distance from each other.

[0092] A first intermediate layer Z1 of aluminum iron, the majority of which is aluminum, is formed on the Si-rich layer S1 in the direction of the free surface O. Traces of Si, alkaline earth metals and / or transition metals as well as unavoidable impurities may also be contained in the layer S1. The intermediate layer Z1 is nonporous.

[0093] In the direction towards the free surface O, on the intermediate layer Z1 there is a second Si-rich layer S2 .

[0094] A second intermediate layer Z2 is formed on the second Si-rich layer S2 in the direction toward the free surface O. The second intermediate layer Z2 is also composed of aluminum iron, most of which is aluminum, and alkaline earth metals and / or transition metals may also be present. It may also contain trace amounts of Si and other unavoidable impurities. The second intermediate layer Z2 is also non-porous.

[0095] The second intermediate layer Z2 is covered on its side facing the free surface O with an oxide layer OX, which consists essentially of aluminum, silicon and alkaline earth metal and / or transition metal oxides. In this case, an oxide layer thickness of up to 1.5 μm can be present on average on the hot-formed component. The surface of the oxide layer OX formed on the free surface O of the corrosion protection coating K forms crater-shaped pores P2 that are open to the surroundings in a small number and at large distances from each other.

[0096] For comparison, components were formed from flat steel products coated with an AlSi coating according to the prior art template described in EP 2 086 755. The coating consisted, in wt. %, of 9.5% Si, 3.5% Fe and the remainder of aluminum and unavoidable impurities, ie contained no alkaline earth metals or transition metals of the type added according to the invention.

[0097] The steel matrix of the flat steel product consists, in % by weight, of 0.224% C, 0.25% Si, 1.16% Mn, 0.014% P, 0.002% S, 0.039% Al, 0.0034% N, 0.2% Cr, 0.03% Ti and 0.0026% B.

[0098] Before the application of the metallic coating and the forming into the flat steel products, the flat steel products processed for comparison were annealed in a continuous furnace with four zones, with the dew point temperatures TP and annealing temperatures GT set as given in Table 6. The air ratio λ in the continuous furnace was 0.98.

[0099] A five-layer corrosion protection coating was also provided in a conventional component produced for comparison. However, it was found that, relative to the number of pores in the coating of the conventional component produced for comparison, the number of pores P2 in the oxide layer OX in the component produced according to the invention was reduced by at least 25% and the number of pores P1 in the diffusion layer D was reduced by at least 40% compared to the pores present in the corresponding layers of the corrosion protection coating of the conventional component produced for comparison. After a residence time of 600 s in the oven, the area occupied by the pores P1 in the layer D was 300 μm at a measuring length of 500 μm. 2 .

[0100] The reduction of P2 holes leads to the reduction of paint pits and improves adhesion and welding performance. The P2 hole has an opening of several nm towards the atmosphere. If the component is further processed after hot forming, it is usually processed by the automobile, in addition to a large number of cleaning steps. Contact with water-based solutions is inevitable. During cleaning, water can invade the holes P2 of the layer because the surfactant added to the clean water improves wettability and significantly reduces the surface tension of water. In the process of cathode dip painting, water may also invade the open holes P2. In this special case, the clean water also causes the separation of paint particles, and the paint particles cannot invade the holes P2 due to the size of the opening. When baking the paint layer, the water present in the hole P2 reaches the boiling point, which leads to a vapor phase, which explodes through the paint to the surrounding environment in a boiling-delayed manner. So-called paint pits are formed by these reactions, which, in addition to visual effects, also significantly reduce the effect of the paint in terms of corrosion protection. Especially for aluminum-based coatings, corrosion and rust (lackunterwanderung) at the bottom of the paint can be caused on such a position. Particularly troublesome for further processing is the occurrence of red rust, which forms due to the high iron content of the coating and stands out visually.

[0101] Moreover, in the case of a surface with many openings P2, the adhesive cannot enter the holes P2 due to its higher viscosity. This can lead to incomplete coverage of the surface by the adhesive. Cavities are also formed in the area of ​​the holes, as a result of which the adhesion is also deteriorated.

[0102] The pores P2 present in the layer OX also lead to altered current paths in the material during resistance spot welding, which adversely affects the welding performance.

[0103] In the case of a high number of pores, there is also an enlarged surface at which water can decompose during oxidation in the hot forming process. In this way, diffused hydrogen can penetrate the material, which is known to increase the risk of hydrogen-induced crack formation.

[0104] By minimizing the frequency of occurrence of holes P2 achieved in the production of sheet metal components according to the invention, the risks associated with hole formation in conventionally produced components can be effectively reduced.

[0105] A reduction in the number of pores P1 in the diffusion layer D also leads to an increase in the forces that can be transmitted in the adhesive connection and to an improvement in the welding properties.

[0106] The P2 holes represent cavities in the corrosion protection coating K. In the case of an excessively high number of holes, there is the risk that the corrosion protection coating K breaks in the boundary region between the diffusion layer D and the first Si-rich layer S1, so that the adhesive joint also fails prematurely. With the reduction in the number of holes P1 achieved according to the invention, the area through which the force of the adhesive connection is transmitted is increased by more than 60%, and the risk of delamination fracture is thus correspondingly reduced.

[0107] In order to demonstrate the effect of the invention, cold-rolled steel sheets each having a thickness of 1.5 mm were produced in a conventional manner from six steels ST1 to ST6 (whose compositions are given in Table 1) (working step a) of the method according to the invention).

[0108] In nine tests V1-V9, the steel sheets thus provided were subjected to continuous annealing G1, G2 or G3 in a continuous furnace having four consecutive zones A, B, C, D. The dew point temperatures TP set in zones AD in the annealing variants G1-G3 are given in Table 2. A -TP D , annealing temperature GT A -GT D and the hydrogen content H2 and nitrogen content N2 of the respective annealing atmosphere, the remainder consisting of technically unavoidable impurities (working step b) of the method according to the invention).

[0109] The samples annealed in this way were each coated in a conventional manner with an Al-based corrosion protection coating Z1-Z5 in a coverage weight AG. The compositions of the corrosion protection coatings Z1-Z5 are given in Table 3 (working step c) of the method according to the invention).

[0110] In tests V1-V9, the samples provided with the corrosion protection coatings Z1-Z5 were heated in a continuous furnace to the hot forming temperature T WU , at this temperature, to maintain time t WU These samples are retained (working step f) of the method according to the invention).

[0111] Steels ST1-ST6 constituting the samples used in tests V1-V9, annealing variants G1-G3 used in tests V1-V9, compositions Z1-Z5 of the corrosion protection coatings produced in tests V1-V9 and their corresponding covering weights AG, and hot forming temperatures T selected in tests V1-V9 WU and hold time t WU It is shown in Table 4.

[0112] The samples heated in this way were removed from the continuous furnace within a corresponding transfer time of 3-7 seconds and placed in a conventional hot forming tool, where they were hot formed into components. Subsequently, they were cooled to room temperature at 270 K / s (working steps g) and h) of the method according to the invention).

[0113] Three cross-sectional slices were produced in a manner known per se from the components obtained in experiments V1 to V9, which were etched with 3% nitric acid (Nital) in order to illustrate the layer structure. Figure 1 , a diagram of a cross-sectional grinding slice with a magnification of 500 times is produced. In the corresponding diagram, the holes P1, P2 present in the layers OX and D are counted over a length section of 550 μm. The arithmetic mean is formed from the count results determined for the three cross-sectional grinding slices of a sample. This arithmetic mean of the numbers determined for the holes P1 and P2 is compared with the comparative value determined in the same way for the comparative sample.

[0114] From this comparison, the relative reduction of the number of pores P1 and P2 obtained by the invention is given in Table 5. Also in Table 5, the share of the paint pits in the total area of ​​the respective samples, the reduction of the delamination area and the weld area determined according to the steel testing manual SEP1220-2 are indicated. The weld area greater than 1 kA has been classified as "normal".

[0115] Table 1

[0116] steel C Si Mn P S Al Nb Ti B A 0.08 0.33 0.95 0.025 0.02 0.013 0.09 0.01 0.005 B 0.23 0.38 1.3 0.02 0.007 0.013 - 0.03 0.004 C 0.38 0.37 1.38 0.02 0.008 0.013 - 0.1 0.005 D 0.2 0.35 1.35 0.02 0.008 0.012 - 0.02 0.004 E 0.14 0.25 1.07 0.1 0.001 0.08 0.025 0.01 0.002 F 0.24 0.3 1.3 0.022 0.008 0.012 - 0.02 0.004

[0117] In weight %, the balance is Fe and unavoidable impurities

[0118] Table 2

[0119]

[0120] Table 3

[0121] Corrosion protection coating Mg Si Fe Z1 0.3 9.5 3 Z2 0.5 8 3.5 Z3 0.1 10 3 Z4 2 8 2 Z5 0.8 8 3

[0122] In weight %, the balance is Al and unavoidable impurities

[0123]

[0124]

[0125] Table 5

[0126]

[0127] Table 6

[0128]

Claims

1. A method for producing a sheet metal component from a flat steel product provided with a corrosion protection coating, the method comprising the following working steps: a) providing a flat steel product produced from a steel consisting, in wt. %, of 0.07-0.5% C, 0.4-3% Mn, 0.06-1.7% Si, up to 0.06% P, up to 0.01% S, up to 1.0% Al, up to 0.15% Ti, up to 0.6% Nb, up to 0.01% B, up to 1.0% Cr, up to 1.0% Mo, the sum of the contents of Cr and Mo being at most 1.0%, up to 0.2% Ca, up to 0.1% V and the remainder being iron and unavoidable impurities; b) annealing the flat steel product in a continuous furnace having four zones A, B, C and D, through which the flat steel product passes continuously and in which the flat steel product is annealed at a temperature having a dew point temperature TP A TP B TP C TP D The annealing temperature is GT A GT B GT C GT D Annealing, the annealing atmosphere is composed of 0.1-15 volume % hydrogen and the balance nitrogen and technically unavoidable impurities, satisfying the following conditions: c) applying a corrosion protection coating to the flat steel product obtained in working step b), wherein: The corrosion protection coating consists, in weight %, of up to 15% Si, up to 5% Fe, a total of 0.1-5% of at least one alkaline earth metal or transition metal, and the remainder of Al and unavoidable impurities; d) Optionally: temper rolling a flat steel product provided with a corrosion protection coating; e) optionally: dividing slabs from the flat steel product; Heating the flat steel product or slab to a hot forming temperature which is above the Ac3 temperature of the steel of the flat steel product and does not exceed 1000° C. for a holding time which is sufficient to introduce a thermal energy Js of more than 100 000 kJs and at most 800 000 kJs into the flat steel product or slab; f) hot forming a flat steel product heated to a hot forming temperature or a slab heated to a hot forming temperature into a sheet metal component; g) cooling at least a section of the component at a cooling rate sufficient to produce a quenched structure in said section of the sheet material component.

2. The method according to claim 1, characterized in that The thickness of the flat steel product provided in working step a) is 0.6-7 mm.

3. The method according to any one of the preceding claims, characterized in that In the annealing performed in step b), the annealing temperature GT is 100°C in zone A of the continuous furnace. A 810-940℃ and dew point temperature TP A -15℃ to -25℃.

4. The method according to any one of the preceding claims, characterized in that In the annealing performed in step b), the annealing temperature GT in zone B of the continuous furnace is B It is 800-900℃.

5. The method according to any one of the preceding claims, characterized in that In the annealing performed in working step b), the annealing temperature GTc in zone C of the continuous furnace is 800-920° C. and the dew point temperature TP C -30℃ to -50℃.

6. The method according to any one of the preceding claims, characterized in that During the annealing performed in step b), the annealing temperature GT in zone D of the continuous furnace is D It is 780-930℃.

7. The method according to any one of the preceding claims, characterized in that During the annealing performed in step b), the annealing atmosphere maintained in the region AD has a lambda value of 0.95-1.

1.

8. The method according to any one of the preceding claims, characterized in that The Si content of the corrosion protection coating applied to the flat steel product in working step c) is at least 3% by weight.

9. The method according to any one of the preceding claims, characterized in that The Fe content of the corrosion protection coating applied to the flat steel product in working step c) is at least 1% by weight.

10. The method according to any one of the preceding claims, characterized in that The corrosion protection coating applied to the flat steel product in working step c) contains a total amount of at least 0.11% by weight of alkaline earth metals or transition metals.

11. The method according to any one of the preceding claims, characterized in that The content of the at least one alkaline earth metal or transition metal in the corrosion protection coating applied to the flat steel product in working step c) amounts to a maximum of 0.6% by weight.

12. The method according to any one of the preceding claims, characterized in that The corrosion protection coating applied to the flat steel product in working step c) contains magnesium as at least one alkaline earth metal or transition metal.

13. The method according to any one of the preceding claims, characterized in that The coverage weight of the corrosion protection coating applied to the flat steel product in working step c) is 30-100 g / m per coated side of the flat steel product. 2 .

14. The method according to any one of the preceding claims, characterized in that In working step c), the application of the corrosion protection coating is carried out by hot-dip coating.

15. The method according to any one of the preceding claims, characterized in that In working step f), the flat steel product or slab is heated in a continuous furnace by radiant heat and is kept heated for a period of 100 to 900 seconds.

16. Sheet metal component manufactured from a flat steel product, the steel substrate of which consists of a steel which, in wt. %, consists of: 0.07-0.4% C, 0.5-3% Mn, 0.06-1.7% Si, up to 0.06% P, up to 0.01% S, up to 1.0% Al, up to 0.15% Ti, up to 0.6% Nb, up to 0.01% B, up to 1.0% Cr, up to 1.0% Mo, wherein the sum of the contents of Cr and Mo is up to 1.0%, up to 0.2% Ca, up to 0.1% V and the balance of iron and unavoidable impurities, and the steel substrate is coated with a corrosion protection coating, the corrosion protection coating consisting, in weight %, of Up to 15% Si, up to 5% Fe, a total amount of 0.1-5% by weight of at least one alkaline earth metal or transition metal and the remainder Al and unavoidable impurities, wherein the layer of the corrosion protection coating adjacent to the steel substrate is a boundary diffusion layer (D) consisting of ferrite with an Al content of up to 50% by weight, wherein in the cross section of the boundary diffusion layer (D), the proportion of the area occupied by pores with a diameter of ≥ 0.1 μm is less than 10%, and wherein the area occupied by pores in the boundary diffusion layer (D) over a measuring length of 500 μm is <300 μm 2 .

17. The sheet material member according to claim 16, characterized in that The boundary diffusion layer (D) has a thickness of 1-30 μm.

18. The sheet material member according to claim 16, characterized in that The thickness of the interface diffusion layer is 2-20 μm.

19. The sheet material member according to claim 16, characterized in that The thickness of the interface diffusion layer is 4-16 μm.

20. The sheet material member according to claim 16, characterized in that The Mn content in the steel of the steel base material of the flat steel product for producing the sheet metal component is 0.8 to 2.5% by weight.

21. The sheet material member according to claim 16, characterized in that The Mn content in the steel of the steel base material of the flat steel product for producing the sheet metal component is 1.0 to 2.0% by weight.

22. The sheet material member according to claim 16, characterized in that The Mn content in the steel of the steel base material of the flat steel product for producing the sheet metal component is 1.0 to 1.5% by weight.

23. The sheet material member according to claim 16, characterized in that The Si content in the steel of the steel base material of the flat steel product for producing the sheet metal component is 0.06 to 1.1% by weight.

24. The sheet material member according to claim 16, characterized in that The Si content in the steel of the steel substrate of the flat steel product for producing the sheet metal component is 0.06 to 0.9% by weight.

25. The sheet material member according to claim 16, characterized in that The Si content in the steel of the steel substrate of the flat steel product from which the sheet metal component is produced is 0.3 to 0.4% by weight.

26. The sheet material member according to claim 16, characterized in that The P content in the steel of the steel base material of the flat steel product for producing the sheet metal component is at most 0.03% by weight.

27. The panel assembly according to claim 16, characterized in that The Al content in the steel of the steel base material of the flat steel product for producing the sheet metal component is at most 0.5% by weight.

28. The sheet material member according to claim 16, characterized in that The Al content in the steel of the steel base material of the flat steel product from which the sheet metal component is produced is at most 0.1% by weight.

29. The sheet material member according to claim 16, characterized in that The Al content in the steel of the steel base material of the flat steel product from which the sheet metal component is produced is at most 0.05% by weight.

30. The sheet material member according to claim 16, characterized in that The Nb content in the steel of the steel base material of the flat steel product for producing the sheet metal component is at most 0.1% by weight.

31. The sheet material member according to claim 16, characterized in that The B content in the steel of the steel base material of the flat steel product for producing the sheet metal component is at most 0.005% by weight.

32. The sheet material member according to claim 16, characterized in that The Cr content in the steel of the steel base material of the flat steel product for producing the sheet metal component is at most 0.5% by weight.

33. The sheet material member according to claim 16, characterized in that The chromium content of the steel substrate from which the flat steel product from which the sheet metal component is produced is at most 0.2% by weight.

34. The sheet material member according to claim 16, characterized in that The Mo content in the steel of the steel substrate of the flat steel product for producing the sheet metal component is at most 0.5% by weight.

35. The sheet material member according to claim 16, characterized in that The Mo content in the steel of the steel base material of the flat steel product for producing the sheet metal component is at most 0.2% by weight.

36. The sheet material member according to claim 16, characterized in that The anticorrosion coating consists, in weight %, of up to 11% Si, up to 4% Fe, a total amount of 0.11-1.5% by weight of at least one alkaline earth metal or transition metal, and the remainder of Al and unavoidable impurities by weight.

37. The sheet material member according to claim 16, characterized in that The anti-corrosion coating is composed of 8.5-11% Si, 1-3.5% Fe, 0.11-0.6% by weight of at least one alkaline earth metal or transition metal, and the remainder of Al and inevitable impurities by weight.

38. The sheet material member according to claim 16, characterized in that The layer of the anti-corrosion coating adjacent to the steel substrate is a boundary diffusion layer (D) consisting of ferrite with an Al content of 1-50 wt%.

39. The sheet material member according to claim 16, characterized in that In the cross section of the boundary diffusion layer (D), the proportion of the area occupied by pores with a diameter ≧0.1 μm is less than 5%.

40. The sheet material member according to claim 16, characterized in that In the cross section of the boundary diffusion layer (D), the proportion of the area occupied by pores with a diameter ≧0.1 μm is less than 3%.

41. The sheet material member according to claim 16, characterized in that The area occupied by the pores in the boundary diffusion layer (D) is < 200 μm over a measuring length of 500 μm 2 .

42. The sheet material member according to claim 16, characterized in that The area occupied by the pores in the boundary diffusion layer (D) is <100 μm over a measuring length of 500 μm 2 .

43. The sheet material member of claim 16, wherein the steel substrate of the sheet material member consists of steel, wherein the steel consists, in weight %, of: 0.07-0.4% C, 1.5-1.5% Mn, 0.3-0.4% Si, up to 0.03% P, up to 0.01% S, up to 0.05% Al, up to 0.15% Ti, up to 0.6% Nb, up to 0.005% B, up to 0.5% Cr, up to 0.5% Mo, wherein the sum of the contents of Cr and Mo is up to 0.5%, the balance being iron and unavoidable impurities, and the steel substrate is coated with a corrosion protection A corrosion protection coating, wherein the corrosion protection coating is composed, in weight %, of up to 3-11% Si, up to 5% Fe, a total content of 0.11-0.6% by weight of at least one alkaline earth metal or transition metal, the remainder of Al and unavoidable impurities; in the cross section of the boundary diffusion layer (D), the proportion of the area occupied by pores with a diameter of ≥ 0.1 μm is less than 3%, and the area occupied by pores in the boundary diffusion layer (D) is < 200 μm over a measuring length of 500 μm 2 .